STRATEGI PROMOSI PRODI JURNALISTIK ISLAM MELALUI PENYEBARAN OPINI DI MEDIA SOSIAL PADA PENERIMAAN MAHASISWA BARU UIN MAHMUD YUNUS BATUSANGKAR - Tiara Aprilia; Zafirah Quroatun ÔÇÿUyun (KINEMA: Jurnal Komunikasi dan Penyiaran, 2023)
The main problem in this thesis is what promotion strategy is used by the Islamic Journalism Study Program in promoting its new study program. The purpose of this study was to find out the appropriate promotion strategy used by the Islamic Journalism Study Program in accepting new students. The type of research used is qualitative research with a descriptive approach. Data collection techniques used were observation, interviews and document review. Data analysis techniques performed, namely data reduction (summarizing, choosing main points, focusing on important things, looking for themes and patterns), data presentation (brief descriptions/charts/relationships between categories/flowcharts/and the like), and drawing conclusions . The technique of guaranteeing the validity of the data used is triangulation. The results of this study can be concluded that the promotion strategy used is socialization or going directly to schools. Second, by spreading opinions on social media, the social media used are Tiktok, Instagram and Tiktok. Furthermore, advertising through social media and print media. Personal Selling by providing affirmation scholarships with UKT 1 relief to the first 10 applicants, which is IDR 400,000. Personal selling is the method that the faculty considers to be the most effective because it is direct (face to face) by visiting schools inside and outside the city. While publicity is a way of using the media to cover faculty activities related to new admissions. Apart from choosing media as an advertising or promotion tool, the media used are social media and print media.